Health seeking behaviours and treatments received by Australian women with vulvodynia: A cross‐sectional survey. (31st August 2021) - Mitchell, Alice M.; Armour, Mike; Chalmers, K. Jane
Abstract : Background: Vulvodynia is a condition characterised by pain in the vulva lasting more than three months and for which no obvious aetiology can be found. It affects around 8% of women and has significant negative impacts on quality of life. There is a paucity of research on healthcare management pathways and the use of evidence‐based treatments in an Australian community setting. Aims: To explore which healthcare professionals Australian women with vulvodynia seek treatment from, and which treatments are recommended, provided, or prescribed by these healthcare professionals. Materials and Methods: A cross‐sectional online survey was conducted from May 2019 to August 2019. Women were eligible to participate if they had been diagnosed with vulvodynia by a healthcare professional, were currently living in Australia, and were over 18 years old. Results: Fifty respondents meet the inclusion criteria, with a mean age of 30.5 years. On average, respondents reported seeing four different types of healthcare professionals in the management of their vulvodynia, with general practitioners (GPs) (98%), medical specialists (96%), and physiotherapists (80%) being the three most commonly consulted. Most respondents reported seeing multiple GPs (>87%), multiple medical specialists (>77%), and multiple physiotherapists (50%). The most commonly prescribed interventions were pelvic floor down‐training exercises (76%), topical (70%) and oral (70%) medication, and vulvodynia information (56%). Conclusions: Australian women with vulvodynia seek help from several professionals and receive a variety of treatments for their pain. Of concern is many treatments that are being offered clinically have very little peer‐reviewed evidence of effectiveness in vulvodynia.